2020
DOI: 10.1177/0033354920912713
|View full text |Cite
|
Sign up to set email alerts
|

State-Level Prevalence of Bullying Victimization Among Children and Adolescents, National Survey of Children’s Health, 2016-2017

Abstract: Bullying is a serious public health issue among children and adolescents in the United States. The purpose of this study was to estimate the prevalence of bullying victimization (defined as a child being bullied, picked on, or excluded by children) in the 50 states and the District of Columbia. We used data on bullying victimization from the 2016-2017 National Survey of Children’s Health (NSCH). We stratified the sample by age: children aged 6-11 years (n = 21 142) and adolescents aged 12-17 years (n = 29 011)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In the current study, the prevalence of caregiver-reported bullying victimization was 15.3%, which is lower than the 22.4% of children aged 6-11 reported in the National Survey of Children's Health (Lebrun-Harris et al, 2020). Consistent with previous studies (Serafini et al, 2021), the prevalence of any NSSI or suicidality was higher among those being bullied (18.2%) compared to their non-bullied peers (7.4%).…”
Section: Prevalence Of Bullying Victimization Nssi and Suicidality In...supporting
confidence: 81%
“…In the current study, the prevalence of caregiver-reported bullying victimization was 15.3%, which is lower than the 22.4% of children aged 6-11 reported in the National Survey of Children's Health (Lebrun-Harris et al, 2020). Consistent with previous studies (Serafini et al, 2021), the prevalence of any NSSI or suicidality was higher among those being bullied (18.2%) compared to their non-bullied peers (7.4%).…”
Section: Prevalence Of Bullying Victimization Nssi and Suicidality In...supporting
confidence: 81%
“…Large-scale surveys using internationally standard methodology to investigate teenager bullying victimization are still mainly limited to European and other Western countries (Chester et al, 2015; Lebrun-Harris et al, 2020; Lian et al, 2018). Considering the lack of large-sample research in China, the current study is based on a large sample of Chinese students.…”
Section: Introductionmentioning
confidence: 99%
“…The US Census Bureau employed a two‐phase data collection approach (Lebrun‐Harris et al, 2020). First, the participants completed an initial household screener, which included basic demographic characteristics and special healthcare needs of all children in the household.…”
Section: Methodsmentioning
confidence: 99%